2022
DOI: 10.1093/ageing/afac168
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of geriatric assessments on the association between chronic kidney disease stages and mortality among older people: a secondary analysis of a multicentre cohort study

Abstract: Background age-adapted definition of chronic kidney disease (CKD) does not take individual risk factors into account. We aimed at investigating whether functional impairments influence CKD stage at which mortality increases among older people. Methods our series consisted of 2,372 outpatients aged 75 years or more enrolled in a multicentre international prospective cohort study. The study outcome was 24-month mortality. Kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For these reasons, guidelines recommend the uACR as the best test to assess albuminuria/proteinuria ( 52 , 53 ). Additionally, ACR can accurately predict cardiovascular endpoints and other endpoints, along with the risk of developing CKD among individuals with high-to-normal eGFR ( 54–57 ). Furthermore, a recent meta-analysis demonstrated that elevated uACR levels are independently associated with an augmented risk of hypertension ( 58 ).…”
Section: Biomarkers Of Kidney Functionmentioning
confidence: 99%
“…For these reasons, guidelines recommend the uACR as the best test to assess albuminuria/proteinuria ( 52 , 53 ). Additionally, ACR can accurately predict cardiovascular endpoints and other endpoints, along with the risk of developing CKD among individuals with high-to-normal eGFR ( 54–57 ). Furthermore, a recent meta-analysis demonstrated that elevated uACR levels are independently associated with an augmented risk of hypertension ( 58 ).…”
Section: Biomarkers Of Kidney Functionmentioning
confidence: 99%
“…Therefore, establishing the association of the glomerular filtration rate with functional performance is important to improve physical functioning. Moreover, there is a clinically relevant interplay between impaired physical performance and CKD, which may affect prognosis in older populations 12 13. However, most previous studies are limited to cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%